2007
DOI: 10.5038/2375-0901.10.4.5
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions of Private Paratransit Operation in Indonesia

Abstract: In this article, public perception is expressed by user participation in rating the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 12 publications
3
45
0
1
Order By: Relevance
“…As mentioned in the introduction, several studies have demonstrated the causal relationship between perceived quality of bus service and customer satisfaction (e.g., Eboli andMazzulla 2007, Joewono andKubota 2007). In view of that finding, in this study, we chose to hypothesize about the possible effect of the perceived quality of bus service on the behavioral intention of non-bus users.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned in the introduction, several studies have demonstrated the causal relationship between perceived quality of bus service and customer satisfaction (e.g., Eboli andMazzulla 2007, Joewono andKubota 2007). In view of that finding, in this study, we chose to hypothesize about the possible effect of the perceived quality of bus service on the behavioral intention of non-bus users.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, research on similar issues regarding the quality of transit service perceived by bus users has confirmed this assumption. For example, Eboli and Mazzulla (2007) found that perceived quality attributes of bus service had an impact on customer satisfaction, and Joewono and Kubota (2007) also found a significant relationship between overall satisfaction and loyalty to use the transit service in the future. Jen and Hu (2003) concluded that passengers' repurchase intentions were determined by their perceived value of the bus service.…”
Section: Introductionmentioning
confidence: 99%
“…That is why recent years have seen the development of derived importance methods based on CSS (Weinstein, 2000;Cavana et al, 2007;Pakdil and Aydin, 2007;Eboli and Mazzulla, 2007;Joewono and Kubota, 2007;Dell'Olio et al, 2010;Nurul--Habib et al, 2011;Jen et al, 2011) and from stated preference surveys (Hensher and Prioni, 2002;Hensher et al, 2003;Eboli and Mazzulla, 2008a;2008b;Dell'Olio et al, 2011;Cirillo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the massive human movement and goods are very necessary in two cities, since high mobility is mandatory to meet the needs (Joewono & Kubota 2007). This high requirement is regarded by the company as a step to develop its products, one of them with the utilization of technology and information systems in corporate strategy.…”
Section: Methodsmentioning
confidence: 99%